Enhanced Cr(VI) removal by nanoscale zerovalent iron through biogenic sulfidation:Comparison against corresponding chemical sulfidation - Yanni Xi; Zheng Peng; Zhuang Zhang; Zhu Su; Yicai Huang; Xin Li; Xingzhong Yuan (Cleaner Chemical Engineering)
This study examines the effects of biogenic sulfidation and chemical sulfidation on the reactivity of nanoscale zerovalent iron (nZVI) for the removal of carcinogenic hexavalent chromium (Cr(VI)). Biogenic sulfidated nanoscale zerovalent iron (BS-nZVI) was synthesised by culturing nZVI with sulphate-reducing bacteria (SRB), while chemically synthesised sulfidated nanoscale zerovalent iron (CS-nZVI) was produced using a Na2S solution. Characterisation results indicated that both BS-nZVI and CS-nZVI were coated with FeSx, with BS-nZVI additionally covered by extracellular polymeric substances (EPS) secreted by the SRB. Both BS-nZVI and CS-nZVI exhibited significantly higher Cr(VI) removal efficiencies compared to nZVI, with values of 18.91 mg/g and 18.80 mg/g, respectively, versus 0.095 mg/g for nZVI. These improvements are attributed to the enhanced electron transfer properties of FeSx. In cyclic “sulfidation-Cr(VI) removal” experiments, biogenic sulfidation was found to be more effective than chemical sulfidation in enhancing and reactivating the Cr(VI) removal capacity of nZVI. The EPS associated with S-nZVI provided additional binding sites for co-precipitation of Cr(III)-Fe(III) during Cr(VI) removal, resulting in the formation of a loosely structured Cr(III)-Fe(III)-EPS co-precipitate. This co-precipitate mitigated the hindering caused by dense Cr(III)-Fe(III) passivation layers on electron transfer during Cr(VI) removal and cyclic sulfidation, in contrast to CS-nZVI. This study elucidates the synergistic effects of the coupled SRB-ZVI system for Cr(VI) remediation.